Development of a fruit flavored-whey beverage - Abalos, Remedios P.; Rillo, Belen O. (1977., 1977)
The development of a fruit-flavored whey beverage was the subject of this study. To obtain such product, the study was divided into three phases. Phase I involved the determination of the most preferred fruit juice-whey powder blend. Four fruit juices were tested for flavoring: strawberry, orange, grape and lemon-lime. As a result of the subjective evaluation, the orange flavored whey beverage was the most preferred blend. The best type of stabilizer was determined in Phase II. The choices were commercial pectin, sodium alginate and carrageenan. The orange-whey beverage stabilized by pectin was found to be the most acceptable with an average acceptability rating of like moderately to like very much. Phase III was centered on the determination of the maximum level of whey which can be incorporated in the beverage. Increasing the levels of whey which correspondingly increase the nutritive value without impairing the desirable qualities was the objective of this study. From the four levels tested, namely, 6.8%, 8.8%, 10.8% and 12.8%, by weight of the beverage, level 6.8% was found by majority of the panelists to be the maximum acceptable level for the beverage.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Beverages